Use of the information gathered during I/M programs to estimate emissions from gasoline vehicles - Huertas, Jorge Ignacio; Mendoza, E.; Córdoba, Jorge (Revista Facultad de Ingeniería Universidad de Antioquia, 2013)
Currently, most of the vehicular emissions inventories developed for large cities are based on the emissions factors developed by the US EPA. Trying to use the US EPA MOBILE tool, the local environmental authorities concentrate their efforts in modifying those emissions factors to take care of the particular characteristics of each city. However, there is still a need for a methodology based on experimental tests to improve the accuracy of the emissions inventories developed for large cities. To address this need, the present work proposes a methodology to improve the accuracy of the vehicular emissions inventory using the information gathered during the inspection and maintenance (I/M) programs where the emissions of 100% of the vehicular fleet is evaluated using the ASM 5015, ASM 2525 or similar type of tests. Experimental work on road and on a chassis dynamometer was developed to explore the feasibility of implementing such methodology for the case of the constant speed mode of operation in a particular type of car. Preliminary results show that the proposed methodology has the potential to be implemented for the case of constant speed mode of operation.